Chylothorax post transaxillary first rib resection for thoracic outlet syndrome. Issue 3 (8th March 2021) - Bowden, Sylvie; Firdouse, Mohammed; Roche-Nagle, Graham
Abstract : We present a patient who developed high output chyle leak post left transaxillary first rib resection for venous thoracic outlet syndrome. The high output chylorrhoea was successfully treated by conservative measures, bed rest, parenteral nutrition and low-fat diet. The patient was discharged after an 18-day hospital stay with a complete resolution of his chylous fistula prior to discharge. This is the first documented chylothorax post transaxillary first rib resection likely due to anomalous chyle anatomy.